2009
DOI: 10.1007/s00011-009-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene and endothelial nitric oxide synthase gene polymorphisms in Behçet’s disease with or without ocular involvement

Abstract: The ACE gene polymorphism does not play a role in the pathogenesis of BD. The findings of the eNOS gene polymorphisms confirmed the significant association with BD and even more in patients with ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][22][23][24] Three studies were excluded because they did not investigate healthy controls. [22][23][24] Thus, 12 studies met the inclusion criteria.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15][16][22][23][24] Three studies were excluded because they did not investigate healthy controls. [22][23][24] Thus, 12 studies met the inclusion criteria.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…[22][23][24] Thus, 12 studies met the inclusion criteria. [5][6][7][8][9][10][11][12][13][14][15][16] These studies comprised four on Behçet's disease (BD), four on Henoch-Schenlein purpura (HSP), three on Kawasaki disease (KD), and one Wegener's granulomatosis (WG). They consisted of six Asian, four Turkish, and two European studies, and in total, they included 1184 cases and 1464 controls.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study by kara et al reported no significant difference in the distribution of the allele and genotype frequencies of the Glu298Asp polymorphism between 92 patients with BD and 100 healthy controls from Turkey (Kara et al, 2006). On the other hand, in Turkey, a strong association of the 4a4b polymorphism with BD was reported (Karasneh et al, 2005;Dursun et al, 2009), and no significant difference was observed in the distribution of the allele and genotype frequencies of the Glu298Asp polymorphism between patients with BD and control subjects (Karasneh et al, 2005). Nakao et al (2007) did not find an association between the Glu298Asp, the 4a4b and À786T>C polymorphisms and BD in Japan.…”
Section: Discussionmentioning
confidence: 97%
“…7 Furthermore, the 4b ⁄ a polymorphism has been also reported to be associated with reduced NO concentrations in plasma. 8 Both these polymorphisms have been associated with BD by some authors, but by no means in all, [9][10][11][12][13][14][15][16] which may be due to small sample sizes, low statistical power and ⁄ or clinical heterogeneity. Therefore, to overcome the limitations of individual studies, resolve inconsistencies and reduce the likelihood that random errors are responsible for false-positive or false-negative associations, we turned to meta-analysis.…”
Section: Introductionmentioning
confidence: 99%